2019
DOI: 10.1007/s00168-019-00933-y
|View full text |Cite
|
Sign up to set email alerts
|

Location choices of Swedish independent schools

Abstract: This paper studies the location decisions of the Swedish privately provided independent schools. It makes use of the great expansion of such schools following the 1992 independent school reform, to study the local determinants of independent school entry. The analysis thus provides evidence on the location choices made by private agents in a mixed market setting. The modifiable areal unit problem is addressed by employing a set of alternative measures for local school markets, constructed from highly detailed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…As regards teachers' labor market choices, Essay IV shows that proximity to schools constitutes an important determinant for the workplace choices of teachers. Given that Edmark (2019) has shown that private schools tend to choose their locations strategically, it may be important to understand the extent to which such location choices are dependent on the composition of the teachers living nearby, and whether the mobility of teachers to such new schools affects students in the schools from which these teachers move. Although there is an association between teacher mobility and student achievement, no studies have examined the feedback dynamics between these two factors using the type of mechanism-based approach advocated in this thesis.…”
Section: Discussionmentioning
confidence: 99%
“…As regards teachers' labor market choices, Essay IV shows that proximity to schools constitutes an important determinant for the workplace choices of teachers. Given that Edmark (2019) has shown that private schools tend to choose their locations strategically, it may be important to understand the extent to which such location choices are dependent on the composition of the teachers living nearby, and whether the mobility of teachers to such new schools affects students in the schools from which these teachers move. Although there is an association between teacher mobility and student achievement, no studies have examined the feedback dynamics between these two factors using the type of mechanism-based approach advocated in this thesis.…”
Section: Discussionmentioning
confidence: 99%
“…Such effects exist in other educational markets. For instance, scholars analyzed the effect on the school educational market from the implementation of vouchers in the USA (Epple and Romano, 1998), from the appearance of charter schools in the USA (Ferreyra and Kosenok, 2018;Cordes, 2018) and independent schools in Sweden (Wondratschek et al, 2013;Edmark, 2019).…”
Section: The Russian University Excellence Initiative In the Context Of Other Excellence Initiativesmentioning
confidence: 99%
“…Although all schools must be open to anyone who applies, private schools are incentivized to attract high-ability students, and may influence the pool of applicants by locating in areas with certain socioeconomic or ethnic profiles, and targeting information at specific groups of parents (see Jennings, 2010 for a U.S. case). Swedish private schools tend to locate in more densely populated municipalities, in areas with high portions of students with highly educated parents, and in areas with higher-than-average proportions of immigrants (Edmark, 2019).…”
Section: Institutional Context: Swedenmentioning
confidence: 99%